Collaborative Forest Management in Uganda - Recommendations for CSOs - Ssemmanda, R.; Kiyingi, G.; Opige, M. (2020)
As part of a multi-country review of community forest rights, Ecological Trends Alliance set out to assess the outcomes of the Collaborative Forest Management model in Uganda; identify factors that influence its success; and discuss strategies that can be undertaken by CSOs to improve the outcomes of CFM. In this policy brief we summarize some of the main outcomes of the review, and the consequent recommendations for CSOs.